2014
DOI: 10.4028/www.scientific.net/msf.778-780.639
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Vapor-Liquid-Solid Selective Epitaxy of Highly p-Type Doped 4H-SiC: PiN Diodes with Peripheral Protection and Improvement of Specific Contact Resistance of Ohmic Contacts

Abstract: This work deals with two applications of the Selective Epitaxial Growth of highly p-type doped buried 4H-SiC in Vapor-Liquid-Solid configuration (SEG-VLS). The first application is the improvement of the Specific Contact Resistance (SCR) of contacts made on such p-type material. As a result of the extremely high doping level, SCR values as low as 1.3x10-6Ω.cm2have been demonstrated. Additionally, the high Al concentration of the SEG-VLS 4H-SiC material induces a lowering of the Al acceptor ionization energy do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Along the recent years, the Vapor-Liquid-Solid (VLS) selective epitaxy [1] has been investigated as an alternative solution to ion implantation for the localized p-type doping of 4H-SiC, leading to considerable reduction of the p-type material resistivity and improvement of the ohmic contacts formed on it, reaching specific contact resistance values as low as 1.3×10 -6 Ω.cm 2 [2]. The next target has been to obtain reliable 4H-SiC P/N junction fabricated using this method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along the recent years, the Vapor-Liquid-Solid (VLS) selective epitaxy [1] has been investigated as an alternative solution to ion implantation for the localized p-type doping of 4H-SiC, leading to considerable reduction of the p-type material resistivity and improvement of the ohmic contacts formed on it, reaching specific contact resistance values as low as 1.3×10 -6 Ω.cm 2 [2]. The next target has been to obtain reliable 4H-SiC P/N junction fabricated using this method.…”
Section: Introductionmentioning
confidence: 99%
“…The next target has been to obtain reliable 4H-SiC P/N junction fabricated using this method. However, up to now, a post growth annealing at high temperature (1700°C) was required in order to obtain direct bias threshold voltages close to the desired value ~ 3 V (expected for a true 4H-SiC P-N junction).Without annealing, this threshold voltage value was remaining in the 1 -2V range [2]. The main goal of the present work has been to define growth conditions allowing the recovery of the targeted threshold voltage of 3 V without the need of high temperature annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have revealed that Vapor-Liquid-Solid (VLS) selective epitaxy can be an interesting method to obtain localized highly p-type doped SiC, leading to considerable reduction of the p-type SiC resistivity and of the specific resistance of the ohmic contacts formed on it. Specific resistance values as low as 1.3×10 -6 Ω.cm 2 have been demonstrated previously [3].…”
Section: Introductionmentioning
confidence: 64%
“…The contact is already ohmic without post-metallization annealing. Specific contact resistances as low as 1.3×10 -6 Ω.cm 2 have been obtained after 500-800°C Rapid Thermal Annealing [16].…”
Section: Vapor-liquid-solid Growthmentioning
confidence: 99%